Population Pharmacokinetics and Pharmacodynamics of Isoniazid and its Metabolite Acetylisoniazid in Chinese Population - Chen, Bing; Shi, Hao-Qiang; Feng, Meihua Rose; Wang, Xi-Han; Cao, Xiao-Mei; Cai, Wei-Min (Frontiers in Pharmacology, 2022)
Objective: We aimed to establish a population pharmacokinetic (PPK) model for isoniazid (INH) and its major metabolite Acetylisoniazid (AcINH) in healthy Chinese participants and tuberculosis patients and assess the role of the NAT2 genotype on the transformation of INH to AcINH. We also sought to estimate the INH exposure that would achieve a 90% effective concentration (EC90) efficiency for patients with various NAT2 genotypes. Method: A total of 45 healthy participants and 157 tuberculosis patients were recruited. For healthy subjects, blood samples were collected 0–14 h after administration of 300 mg or 320 mg of the oral dose of INH; for tuberculosis patients who received at least seven days therapy with INH, blood samples were collected two and/or six hours after administration. The plasma concentration of INH and AcINH was determined by the reverse-phase HPLC method. NAT2 genotypes were determined by allele-specific amplification. The integrated PPK model of INH and AcINH was established through nonlinear mixed-effect modeling (NONMEM). The effect of NAT2 genotype and other covariates on INH and AcINH disposition was evaluated. Monte Carlo simulation was performed for estimating EC90 of INH in patients with various NAT2 genotypes. Results: The estimated absorption rate constant (Ka), oral clearance (CL/F), and apparent volume of distribution (V2/F) for INH were 3.94 ± 0.44 h−1, 18.2 ± 2.45 L⋅h−1, and 56.8 ± 5.53 L, respectively. The constant of clearance (K30) and the volume of distribution (V3/F) of AcINH were 0.33 ± 0.11 h−1 and 25.7 ± 1.30 L, respectively. The fraction of AcINH formation (FM) was 0.81 ± 0.076. NAT2 genotypes had different effects on the CL/F and FM. In subjects with only one copy of NAT2 *5, *6, and *7 alleles, the CL/F values were approximately 46.3%, 54.9%, and 74.8% of *4/*4 subjects, respectively. The FM values were approximately 48.7%, 63.8%, and 86.9% of *4/*4 subjects, respectively. The probability of target attainment of INH EC90 in patients with various NAT2 genotypes was different. Conclusion: The integrated parent-metabolite PPK model accurately characterized the disposition of INH and AcINH in the Chinese population sampled, which may be useful in the individualized therapy of INH.